Application of Metal-Based Nanozymes in Inflammatory Disease: A Review - Li, Ruifeng; Hou, Xinyue; Li, Lingrui; Guo, Jiancheng; Jiang, Wei; Shang, Wenjun (Frontiers in Bioengineering and Biotechnology, 2022)
Reactive oxygen species (ROS) are metabolites of normal cells in organisms, and normal levels of ROS in cells are essential for maintaining cell signaling and other intracellular functions. However, excessive inflammation and ischemia-reperfusion can cause an imbalance of tissue redox balance, and oxidative stress occurs in a tissue, resulting in a large amount of ROS, causing direct tissue damage. The production of many diseases is associated with excess ROS, such as stroke, sepsis, Alzheimer’s disease, and Parkinson’s disease. With the rapid development of nanomedicine, nanomaterials have been widely used to effectively treat various inflammatory diseases due to their superior physical and chemical properties. In this review, we summarize the application of some representative metal-based nanozymes in inflammatory diseases. In addition, we discuss the application of various novel nanomaterials for different therapies and the prospects of using nanoparticles (NPs) as biomedical materials.